Agreement Between a Brief Autism Observational Instrument and Established ASD Measures. (20th May 2016) - Ward, Samantha L.; Sullivan, Karen A.; Gilmore, Linda
Abstract : Objective: Limited time and resources necessitate the availability of accurate, inexpensive and rapid diagnostic aids for Autism Spectrum Disorder (ASD). The Autistic Behavioural Indicators Instrument (ABII) was developed for this purpose, but its psychometric properties have not yet been fully established.Method: The clinician-rated ABII, the Autism Diagnostic Observation Schedule (ADOS), the Childhood Autism Rating Scale – Second Edition, Standard Version (CARS2-ST), and Diagnostic and Statistical Manual of Mental Disorders ( DSM-5 ) diagnostic criteria were individually administered to children with an independent paediatrician DSM-IV-TR or DSM-5 autism spectrum diagnosis, aged 2-6 years ( n = 51, Mchild age = 3.6 years). The agreement between each of the measures on autism diagnostic classification was calculated and compared, and the intercorrelation between the instruments examined.Results: There was significant moderate agreement for the classification of autism between the ABII and the DSM-5, and significant fair agreement between the ABII and ADOS and ABII and CARS2-ST. True positive diagnostic classifications were similar across the ABII ( n = 47, 92.2%) and ADOS ( n = 45, 88.2%), and significantly higher than the CARS2-ST ( n = 30, 58.8%). The ABII total scale score was strongly positively correlated with both the ADOS and CARS2-ST total scores.Conclusion : The ABII's test characteristics were comparable to those of established measures, and the intercorrelations between selected measures support its convergent validity. The ABII could be added to the clinician's toolbox as a screening test.